Calculation of the Ki67 index in pancreatic neuroendocrine tumors: A comparative analysis of four counting methodologies - Reid, Michelle Dian; Bağcı, Pelin; Ohike, Nobuyuki; Saka, Burcu; Erbarut Seven, İpek; Dursun, Nevra; Balcı, Serdar; Gucer, Hasan; Jang, Kee-Taek; Tajiri, Takuma; Baştürk, Olca; Kong, So Yeon; et al. (Nature Publishing Group, 2015)
Ki67 index is now an essential part of classification of pancreatic neuroendocrine tumors. However, its adaptation into daily practice has been fraught with challenges related to counting methodology. In this study, three reviewers used four counting methodologies to calculate Ki67 index in 68 well-differentiated pancreatic neuroendocrine tumors: (1) 'eye-ball' estimation, which has been advocated as reliable and is widely used; (2) automated counting by image analyzer; (3) manual eye-counting (eye under a microscope without a grid); and (4) manual count of camera-captured/printed image. Pearson's correlation (R) was used to measure pair-wise correlation among three reviewers using all four methodologies. Average level of agreement was calculated using mean of R values. The results showed that: (1) 'eye-balling' was least expensive and fastest (average time <1 min) but had poor reliability and reproducibility. (2) Automated count was the most expensive and least practical with major impact on turnaround time (limited by machine and personnel accessibility), and, more importantly, had inaccuracies in overcounting unwanted material. (3) Manual eye count had no additional cost, averaged 6 min, but proved impractical and poorly reproducible. (4) Camera-captured/printed image was most reliable, had highest reproducibility, but took longer than 'eye-balling'. In conclusion, based on its comparatively low cost/benefit ratio and reproducibility, camera-captured/printed image appears to be the most practical for calculating Ki67 index. Although automated counting is generally advertised as the gold standard for index calculation, in this study it was not as accurate or cost-effective as camera-captured/printed image and was highly operator-dependent. 'Eye-balling' produces highly inaccurate and unreliable results, and is not recommended for routine use.
WOS: 000353774200008
PubMed ID: 25412850
Keywords: Ki67 Index; However; Eye-balling